2020
DOI: 10.1155/2020/8065058
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Help-Seeking Behaviours of Patients with Schizophrenia in Rural Cambodia

Abstract: In low- and middle-income countries in Asia, the use of supernatural, religious, and magical approaches to mental illness is widespread. We aimed to document the help-seeking behaviours and barriers to effective mental healthcare in the case of a psychiatric patient in rural Cambodia. The present case report describes the pathway that a patient with schizophrenia utilised to receive effective treatment in a rural area. First, the patient was taken by his parents to a pagoda. Subsequently, they took him to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A study conducted in Pakistan revealed that individuals who perceive a biological cause for the disease were almost 13 times more likely to seek medical help for a relative with schizophrenia than those who gave other reasons for the disease [ 4 ]. A study in Cambodia revealed the community didn't first seek help medical care and Nigerian studies show that most of the participants had visited traditional/faith healers as the first treatment [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Pakistan revealed that individuals who perceive a biological cause for the disease were almost 13 times more likely to seek medical help for a relative with schizophrenia than those who gave other reasons for the disease [ 4 ]. A study in Cambodia revealed the community didn't first seek help medical care and Nigerian studies show that most of the participants had visited traditional/faith healers as the first treatment [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%